Heliotron magnetic system of a fusion neutron source - Kulyk, Yu.S.; Moiseenko, V.Е.; Wauters, T.; Lyssoivan, A.I. (Вопросы атомной науки и техники, 2021)
Results of numerical modelling of electron cyclotron (EC) short pulse wall conditioning discharge are presented. The analysis carried out with the usage of a self-consistent model that simulates radio-frequency (RF) plasma production in stellarator type machines in the ion cyclotron and EC frequency ranges. The discussion of the results of the calculations is presented.